The Effect of Perceived Relative Advantage and E-Commerce Knowledge on The Behavior of Doing Online Business Among Undergraduate Students in Indonesia - Sijabat, Rosdiana (LPPM Universitas BSI, 2024)
Online business endeavors have already become popular due to technological advancements. Many young people engage in online business due to its flexible nature and their technological proficiency. This study investigates the influencing elements in decision-making among young individuals engaging in online business. The results of the study serve as a valuable reference for understanding the crucial factors that drive online business activities among the younger generation. This quantitative study utilizes distributed surveys via Google Forms with 102 respondents. It used the Partial Least Squares Structural Equation Modeling (PLS-SEM) data analysis technique. The results indicate that Perceived Relative Advantage (PRA) significantly influences E-commerce Knowledge (KNOW), which in turn positively influences Actual Action in Doing Online Business (ACTION). Additionally, E-commerce Knowledge (KNOW) mediates the relationship between Perceived Relative Advantage (PRA) and Actual Action in Doing Online Business (ACTION).